The role of leadership in digital transformation in the financial services sector - Gcelu, Nikitha Gita (My University, 2020)
The financial services sector falls within the top three industries that are most susceptible to digital disruption globally. The rise in new digital technologies has transformed business models and how organisations operate – making digital transformation and leadership a key imperative for financial services organisations. Additionally, the recent global pandemic (COVID-19) has accelerated the pace of digital transformation for many organisations and has resulted in virtual work environments; where leaders and subordinates must use digital technologies to achieve business objectives. The role of leadership is crucial to digital transformation in financial services organisations. Leaders, both globally and in South Africa, are experiencing similar challenges – and are tasked with the responsibility of finding effective leadership strategies that will ensure that their businesses successfully navigate the complexities brought about by new digital technologies. However, most financial service organisations have struggled to build up the necessary leadership capabilities to aid their organisations effectively in the digital transformation process. This study conducts a detailed literature review on traditional leadership types and introduces the concepts of e-leadership (which considers traditional leadership types and digital factors on leadership). Additionally, the literature review provides a brief overview of digital transformation factors. The study provides insights on factors accounting for the shortage in leadership trends in financial services, the different technology trends in financial services, and leadership strategies for digital transformation in financial services. Both primary and secondary data were analysed to gain these insights – with the analysis based on the thematic approach. The insights show that technology factors have changed work-life, communication, talent management, and the organisation culture. Furthermore, leaders in financial services organisations have to deploy new leadership strategies to effectively lead digital transformation – with a key focus being on building digital capabilities, digital leadership, embracing flexibility, and creating a diverse workforce.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Digital transformation; Digital leadership; Financial services; SDG-8: Decent work and economic growth